Cherax latimanus sp. nov., a new burrow-dwelling freshwater crayfish (Decapoda, Parastacidae) from the mid-Murray River catchment, Australia - Mccormack, Robert B.; Raadik, Tarmo A. (Zootaxa, 2021)
A new species of freshwater crayfish in the southern hemisphere family Parastacidae is described from the Murray Darling Basin (MDB), eastern Australia. The Swamp Yabby, Cherax latimanus sp. nov., is found in the mid-Murray River area of the states of New South Wales and Victoria and is only the third species of Cherax found naturally occurring in the MDB. It is morphologically distinguished from all other species of Cherax by the presence of marginal mesial dactylar basal spines and extensive ventral propodal setation. It is found in sympatry with the widespread but morphologically similar Common Yabby, Cherax destructor Clark, 1936, but can be distinguished by a suite of morphometric and meristic characters that include a broad rostrum lacking an apical spine, very broad chelae with deep punctations on the lateral propodal edge and ventral propodal setation, two prominent dactylar teeth, one mesial carpal spine, dorsal meral spines present, no setae on carpal mesial margin, cervical spines absent or tiny, and by genetic data. Cherax latimanus is further diagnosed by its distinctive biology: it is not found in permanent aquatic habitats such as streams or billabongs, spending the majority of its time in extensive, terrestrial, burrow networks containing some water, in ephemerally wet habitats such as drainage lines, roadside drains, depressions, swamps and cleared areas of pasture in lowland to foothill areas. It is occasionally found in stream habitats but only during large flood events when burrow systems are inundated.